Macroscopic Profile Modification and Microscopic Displacement Mechanism of Weak Gel Flowing in Porous Media - Jian Wang; Bo Kang; Liehui Zhang; Beata Joanna Darowska; Peng Xu (Journal of Chemistry)
In this paper, the flowing mechanism and function on the macroscopic and microscopic scale in the porous media of a widely used weak gel of an acrylamide based polymer crosslinked with chromium(III) were studied. Innovative microscopic plane visualization model was designed for microscopic scale experiment and sand pack physical model for macroscopic scale. The microscopic displacing experiments indicate that weak gel mainly intrudes into big pores rather than small ones, which can improve the conformance horizontally and increase the sweep efficiency benefiting from fluid diversion. Additionally, due to good viscoelasticity of weak gel, the negative pressure effect was formed enhancing oil recovery flow from small pore throats. Results of macroscopic physical sand pack flow experiment indicate positive influence of weak gel on vertical conformance control. Although the high permeable layer was not completely blocked, the oil recovery improved as a result of weak gel movement by continuous water flooding. Experiments results lead to conclusion, the primary function of weak gel is oil displacement, profile modification is secondary, and its effect is temporary.